Rehearsal simulation for antenatal consults - Cheng, Anita; Yuen, Doris; Cristancho, Sayra (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2021)
Background: Rehearsal simulations are patient-specific case-matched tasks performed immediately prior to the actual task, with the objective of improving performance.Objective: How does rehearsal simulation for antenatal consults impact how residents learn to engage in difficult conversations with families?Study Design: Residents in the NICU performed case-matched video recorded rehearsal simulations, followed by actual antenatal consults. The purpose of antenatal consults is to prepare parents expecting a complication with their baby before birth. Questionnaires assessed changes in resident confidence and self-assessment of communication skills. Residents were interviewed for qualitative data to explore the overall impact of rehearsal simulation on their learning and performance.Results: Thirteen residents participated. Rehearsal simulation improved confidence with a more organized approach of medical content and better communication techniques, allowing for a shift of focus from a checklist approach to building rapport and displaying empathy.Conclusions: While rehearsal simulation did not prepare residents for unexpected parent responses, trainees’ increased confidence with medical content organization and communication techniques created space for reflection-in-action and compassionate approaches.